Leading Teams #6: Performing - Carrie N. Baker; Sarah Bush; Laura Greenhaw; Matthew Gold; Rachel Biderman (EDIS, 2025)
As a part of the Leading Teams series, this article explains the performing stage of group development. This article discusses how Extension team leaders and members can produce results during this stage and provides practical recommendations for enhancing team performance and outcomes. Written by Carrie N. Baker, Sarah A. Bush, Laura L. Greenhaw, Matthew Gold, and Rachel Biderman, and published by the UF/IFAS Department of Agricultural Education and Communication, February 2025.